Représentations des relations entre hégémonie et minorités dans trois pièces de théâtre franco-canadiennes - Côté, Nicole (Theatre Research in Canada / Recherches théâtrales au Canada, 2016)
Nicole Côté examines literary representations of Franco-Canadians’ linguistic minorization as they negotiate with hegemonic English. She suggests that Franco-Canadian theatre reflects the self-translation of the minorities through its heterolinguism and stages their linguistic and cultural hybridity. These plays offer heteroglossic representations that bear witness to the multiple tensions of the minority and migrant communities. They represent the cultural/linguistic self-translation at work, reflecting identities torn between the need to forge a stable core and the adaptation necessary to survive as a minority within the hegemonic group. Thus, the plays examined here belong to Franco-Canadian drama not only because of their themes, but also because of their particular code-switching, where French remains the substrate language. These dramatic representations attest, on a formal level, to the vulnerability of French in a minority context, as well as, on a thematic one, to the resilience of minority communities in constant self-translation, as shown in Elephant Wake , by Joey Tremblay; Sex, Lies et les FrancoManitobains , L’année du Big Mac , and Fort Mac , by Marc Prescott; and Rearview , by Gilles Poulin-Denis.